Spontaneous intrauterine pregnancy, post laparoscopic surgery for didelphys uterus with longitudinal vaginal septum, multiple leiomyomas and bilateral proximal tubal block - Agrawal, Prabha; Agrawal, Rahul; Keshri, Pooja; Kothapalli, Sushma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Mullerian duct anomalies (MDAs) are congenital developmental anomalies of the female reproductive tract. Uterine didelphys also known as a double uterus, with two uteri and cervices, and a single or double vagina, is one of the rarest MDA. Uterine leiomyomas are a common finding in the normal uterus but extremely rare in women with MDAs. We present the case and surgical management of a 28 year-old African woman with uterus didelphys with two separate cervix and vagina with multiple leiomyomas and bilateral proximal tubal block. She presented with inability to conceive and dyspareunia and was referred to us with a diagnosis of multiple fibroids uterus. She was managed successfully by a combined hysteroscopic, laparoscopic and vaginal approach with myomectomy and excision of longitudinal vaginal septum. Post procedure she conceived spontaneously after 6 months. Management of this case was a challenge owing to the coexistence of multiple complex malformations and the difficulty in preserving the reproductive potential. The aim of this case report is to expand the available knowledge about this group of females affected with a common diagnosis of leiomyomas, superimposed on an extremely rare MDA, uterine didelphys.